Environmental niche and functional role similarity between invasive and native palms in the Atlantic Forest - Bello, Carolina [UNESP]; Cintra, Ana Laura P. [UNESP]; Barreto, Elisa; Vancine, Maurício Humberto [UNESP]; Sobral-Souza, Thadeu; Graham, Catherine H.; Galetti, Mauro [UNESP] (Springer Nature, 2021)
Invasive species can significantly affect native species when their niches are similar. Ecological and morphological similarities between the invasive Australian palm, Archontophoenix cunninghamiana, and the native palm from the Brazilian Atlantic Forest, Euterpe edulis, suggest that they have similar environmental requirements and functional roles (i.e., the function a species performs in an ecosystem). This similarity raises concerns about how the invasive palm could impact the native species in the present and future. We used spatial (species occurrences) and ecological information (frugivory events) to characterize the environmental niche and functional role of the two palms and assess their overlap. In addition, we predicted the potential area of occurrence of each palm within the Brazilian Atlantic Forest under current and future climate conditions.We estimated the environmental conditions used by the invasive plant based on its native distribution only, and based on all areas where the species is able to establish across the globe. We found that the environmental niches of the two palm species overlap up to 39%, which corresponds to 50% of the current geographic distribution of E. edulis in the Atlantic Forest. In the areas where the two species potentially co-occur, the impact of the invasive species on the native should be influenced by the invasive species interactions with frugivores. We found that the frugivory functional role of the two palms was similar (84% overlap) which suggest that A. cunninghamiana might disrupt the seed dispersal of the native palm. However, co-occurrence between the palms may decline with future climate change, as the potentially environmental suitable area for the invasive palm is predicted to decline by 10% to 55%. Evaluating the similarity in both the environmental niche, of the native and global extent, and the functional role of native and invasive plants provides a detailed understanding of the potential impact of invasive species on native species now and in the future.
Keywords: Archontophoenix cunninghamiana; Biological invasion; Climate change; Euterpe edulis; Functional role; Niche overlap; Plant-animal interactions